# `int (tan^2(y) + 1) dy` Find the indefinite integral.

*print*Print*list*Cite

### 1 Answer

You need to evaluate the indefinite integral and yo need to use the following trigonometric formula `1 + tan^2 y = 1/(cos^2 y).`

Replacing `1/(cos^2 y)` for `1 + tan^2 y` yields:

`int (1 + tan^2 y) dy = int (dy)/(cos^2 y)`

You need to remember that `1/(cos^2 y) = (tan y)'.`

`int (dy)/(cos^2 y) = int (tan y)' = tan y + C`

**Hence, evaluating the given indefinite integral, yields` int (1 + tan^2 y) dy =tan y + C.` **